An acoustofluidic sputum liquefier1. Issue 15 (7th August 2015) - Huang, Po-Hsun; Ren, Liqiang; Nama, Nitesh; Li, Sixing; Li, Peng; Yao, Xianglan; Cuento, Rosemarie A.; Wei, Cheng-Hsin; Chen, Yuchao; Xie, Yuliang; Nawaz, Ahmad Ahsan; Alevy, Yael G.; et al.
<x xml:space="preserve">Abstract</x> The first microfluidic-based on-chip sputum-liquefaction device is demonstrated via an acoustofluidic micromixer.